Are smallholder farmers better or worse off from an increase in the international price of cereals?. (August 2018) - Nakelse, Tebila; Dalton, Timothy J.; Hendricks, Nathan P.; Hodjo, Manzamasso
Highlights: World price increases have a positive effect on rural household welfare. The net welfare effect depends on the international price transmission elasticity. Millet and maize are the major contributors to rural households' welfare gain. Abstract: The effect of agricultural price shocks on household welfare in low-income countries is a major concern for policymakers attempting to reduce poverty rates. This study estimates the impact of an increase in the world cereal price on rural households in Burkina Faso in an agricultural household model framework. We account for imperfect transmission of global prices to local prices as well as supply and demand response of rural households to price signals. The increase in price during the period from 2006 to 2014 is translated to welfare improvement ranging from 0.02 percent for 2006 to 0.06 percent for 2011 for farmers in Burkina Faso.